IMPLEMENTASI MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASI DARING PADA MASA PANDEMI COVID-19 (Studi Kasus Pada Mata Pelajaran PAI di SMK An – Nadwah Tambun Selatan) - Wida Pratiwi; Akmal Rizki Gunawan Hasibuan (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2021)
The objectives of this research are 1) To find out how to implement the online learning model. 2)To find out what factors are the obstacles in the implementation of online learning, and 3) To find outthe supporting factors in the online learning process during the covid-19 pandemic in class xii Smk An- Nadwah Tambun Selatan. his research is a qualitative research with descriptive analysis technique.Analysis of research data obtained from the process of searching and compiling systematically, dataobtained from observations, interviews and the field, namely data collection, data reduction, datapresentation, conclusions and verification. The results showed that, 1) The implementation of theonline learning model in class XII was by utilizing several kinds of applications, the use of one-sheetlesson plans and evaluation of written worksheets that could be taken and collected directly to theschool. 2) The inhibiting factors in the implementation of online learning are the lack of effectivenessand time efficiency, the lack of enthusiasm of students and the lack of students’ understanding of thematerial. 3) Factors supporting online learning, namely, schools facilitate wifi for teachers in schools,and students are given free internet quota.